The bridge of San Luis Rey [videorecording (DVD)] - McGuckian, Mary; Byrne, Gabriel, 1950-; De Niro, Robert; Abraham, F. Murray; Pinon, Dominique; Wilder, Thornton, 1897-1975 (Giant Pictures, 2021)
When the Bridge of San Luis Rey collapses, five travelers fall into the gorge below. Was it an act of God? In a faithful adaptation of Thorton Wilder's classic Pulitzer Prize winning novel, a friar unravels the lives those who died for an answer, upsetting the Inquisition of Peru's articles of faith. Digitally remastered, this star-studded film is restored with 40 minutes of unseen footage.